Long Noncoding RNAs TYMSOS, VASH1-AS1, and LINC01001 Expressions as Biomarkers of β-thalassaemia Severity Among the Malaysian Patients - Norafiza Mohd Yasin; Nur Fatin Aqilah Raman; Siti Aishah Sulaiman; Nurhairulamri Kosnan; Nor Azian Abdul Murad; Ermi Neiza Mohd Sahid; Yuslina Yusoff; Hishamshah Mohd Ibrahim; Zulaiha Muda; Ezalia Esa (The Prodia Education and Research Institute (PERI), 2025)
BACKGROUND: β-thalassaemia has heterogeneous disease severities ranging from mild to trait, and major. Long noncoding RNAs (lncRNAs) are known to regulate microRNAs (miRNAs) and genes, possibly modifying the disease phenotypes. However, limited data exist on the lncRNAs in β-thalassaemia, and no study has yet addressed this gap in Malaysia. Therefore, this study aimed to identify the expression profile of lncRNAs in β-thalassaemia major and trait among Malaysians.METHODS: Case-control study was conducted in two phases at Tunku Azizah Women and Children's Hospital and the Institute of Medical Research, from September 2019 to November 2021. Total of 141 individuals were recruited, comprising β-thalassemia major (MAJOR, n=11), β-thalassemia trait (TRAIT, n=17), and healthy controls (CON, n=113). All participants were genotyped for thalassaemia and assessed for their haemoglobin and red blood cells (RBC) indices. In the first phase, discovery of lncRNA was performed using microarray, and differential expression of lncRNAs (DEL) in MAJOR, TRAIT, and CON groups was identified. Significant lncRNAs were subjected to lncRNA-miRNA prediction, and gene ontology and biological pathway were analyzed. In validation phase, six potential lncRNAs were further validated via using lncRNA polymerase chain reaction (PCR) custom array.RESULTS: Total of 364 DELs were identified in MAJOR group, and 128 DELs were identified in TRAIT group. Between the MAJOR and TRAIT groups, 100 DELs were dysregulated in MAJOR group. Two molecular networks comprising the lncRNA interactions with miRNAs were identified and associated with traits and major phenotypes, resulting in six potential lncRNAs for validation. Among these six lncRNAs, three lncRNAs (TYMSOS, VASH1-AS1, and LINC01001) were reduced in the MAJOR group (fold change (FC)=-6.67, p=0.026; FC=-8.33, p=0.022; and FC=-8.33, p=0.021, respectively).CONCLUSION: Expressions of TYMSOS, VASH1-AS1, and LINC01001 lncRNAs were altered differently between β-thalassaemia major and trait patients. Therefore these lncRNAs may serve as novel biomarkers for β-thalassaemia disease severity in Malaysian population.KEYWORDS: β-thalassaemia, lncRNAs, miRNAs, severity, major, trait, molecular network